Characterization, interaction and failure analysis of lead-free solder bump interconnects - Thong, Chee Meng. (2008)
Environmental legislation and the continuing industrial drive for further miniaturization and improved performance place over increasing demands on electronic packaging materials. The development of new lead-free solder alloys and associated materials to meet the requirements of the next generation of the electronic packages has gained momentum over the last few years. However with the implementation of lead free soldering technology engineers are no longer able to draw upon the tremendous volume of data available for more conventional packaging materials. Furthermore, it is known that the various materials in a electronic joint will interact with each other and the joints microstructure will evolve during service. For this reasons, it is important to develop our understanding of the nature and dynamics of the interfacial interactions between lead-free solder and the associated metallizations and finish materials.